Theoretical analysis of the short-term regulation of human argininosuccinate synthase (ASS1) activity under hemolysis products accumulation - Barannik, T.; Avdieieva , K. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Under hemolysis and free heme accumulation in blood plasma the velocity of arginine synthesis becomes one of the main factors determining the effectiveness of vessels relaxation. Therefore the analysis of putative sites of heme binding with key enzyme of arginine synthesis, human argininosuccinate synthase (ASS1, EC 6.3.4.5), was held. According to results of molecular docking to ASS1 protein (PatchDock tool) the most probable was heme binding to the cavity of enzyme active center through the sites of interaction with substrates, aspartate (Asp124) and citrulline (Ser189), and through АТP binding site (region Ser12-Thr17). The majority of residues (19 of 26), predicted in heme iron neighborhood, were polar but no cysteines were revealed among them including the site of nitrosylation Cys132. Among hydrophobic residues Leu160 should be noted as discovered to be the putative site of heme binding not only by structure analysis but also by protein sequence analysis (HemeBIND tool). The heme could also attach to Ser180 or Thr174 that were phosphorylation sites. The high probability of consequent binding of two or three heme molecules in active center was shown, that would obviously cause total inhibition of ASS1 by blocking of access to substrates of reaction. After heme filled the cavity of active center the further heme binding сould be provided by amino acid residues involved in enzyme oligomerization including Cys337 predicted (COPA tool) as redox-active residue.